Test-rig design for automated evaluation of automotive electro-chemical sensors - Gupta, Shilpa (My University, 2020)
The main aim of this project is the design and development of an automated test-rig for testing automotive electro-chemical sensors. The main targeted sensor is NOx (Compounds of Nitrogen oxide), which is one of the most critical and failure-prone components of exhaust after-treatment system. Based on the gas concentration measurements from these sensors, several actions are taken to reduce the vehicle emissions and comply with required emission guidelines by government. An automated test-rig can perform various combinations of temperature and gas variations on multiple sensors simultaneously while reducing the operating test time compared to manual one. Added to the advantage is the scope of detailed analysis of faulty field sensors thereby increasing the overall productivity. A cRIO (Compact Re-configurable Input Output) is used as the main embedded controller to carry out test command and control, data logging and saving, and communication with sensors and other test-rig hardware components. The test software is developed in LabVIEW (Laboratory Virtual Instrument EngineeringWorkbench). To reduce operating complexity, script-based command files are made to control various test-rig equipment. Finally, a GUI (Graphical User Interface) is developed for user interaction and real-time monitoring during on-going test. A working automated test-rig is successfully developed and its performance is compared to manual operation through a series of tests. The final testing was carried out in a test cell (gas-sealed box) with provision to mount sensors and other accessories like gas inlet/ outlet valves, gas flow controller and pressure sensor. Several test cases were conducted to evaluate three NOx sensors in three different gas environment - air, nitrogen and NOx (489 ppm concentration). The sensors under test corresponded well to the gas variations resulting in NOx and O2 measurements within the expected range of 467 ppm and 20% respectively. The aim of the project is successfully met with around 50% of active operator/ operating time saved by automated test-rig over manual one. In addition, this test-rig removes the intermittent delays of manual maneuvers resulting in better repeatability performance. Due to limitation of resources, some features and test cases could not be incorporated and their implications are further discussed. As a further improvement, additional safety features can be added and the test-rig can be extended for testing other types of sensors.
Keywords: Automotive sensors; Test automation; NOx; Test-rig; cRIO; LabVIEW